Pengaruh Kualitas Pelayanan, Fasilitas, dan Kepercayaan Terhadap Kepuasan Pelanggan (Studi Pada Bengkel H M Understell Kendaraan Roda Empat) - Alimia Ni’matul Maghviro; Budi Wahono; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abtract The purpose of this study was to determine the effect of service quality, facilities, and trust on customer satisfaction at the Understell Workshop for Four-Wheel Vehicles. The data used in this study is primary data by distributing questionnaires to respondents. The population in this study were customers who used the services of HM Understell four-wheeled vehicle repair shop during the research period, namely December 2021 to February 2022 with an average of 4 customers per day so that it can be seen that the population is 308. The sample used in this study uses the theory according to Arikunto (2010) it is known that a population of 308 can be taken from 20% of the population so that the number of samples is 20% x 308 = 61.6 rounded up to 62 customers. While the sampling technique used in this study is based on non-probability sampling method using purposive sampling research with the characteristics of customers who have used workshop services more than 2 times. The results of the study through the F test and T test showed that simultaneously or partially Service Quality, Facilities, and Trust had a significant positive effect with a sig level of 0.000 <0.05 on customer satisfaction. Keyword: Service Quality, Facilities, Trust, and Customer Satisfaction